Auto-CCAFS-MOT: a batch calculator tool for farmers greenhouse gas emissions (GHG) - CGIAR Platform for Big Data in Agriculture (2020)
Leveraging on the CCAFS-MOT version, we developed a new system to calculate GHG emissions for multiple crop events. It was completed in python to facilitate the integration with web applications. User can download soil-data from SoilGrids, explore state-of-art methodologies and interact with experts from CoolFarmTool and CCAFS team.